The Implementation of Learning Administration Supervision Can Improve Teacher Professionalism at Mts Nurul Huda for the 2019/2020 Academic Year : Pelaksanaan Supervisi Administrasi Pembelajaran Dapat Meningkatkan Profesionalisme Guru Mts Nurul Huda Tahun Pelajaran 2019/2020 - suhaibar suhaibar (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
This research is an Oversight Action Research (PTKp). Related to the social studies learning process, the author has carried out the social studies learning process with the material